2017
DOI: 10.1007/s00705-017-3466-2
|View full text |Cite
|
Sign up to set email alerts
|

Preponderance of enterovirus C in RD-L20B-cell-culture-negative stool samples from children diagnosed with acute flaccid paralysis in Nigeria

Abstract: Recently, a reverse transcriptase semi-nested polymerase chain reaction (RT-snPCR) assay was recommended by the WHO for direct detection of enteroviruses in clinical specimens. In this study, we use this assay and a modification thereof to screen acute flaccid paralysis (AFP) samples that had previously tested negative for enteroviruses by the RD-L20B algorithm. Thirty paired stool suspensions collected in 2015 as part of the national AFP surveillance program in different states of Nigeria were analyzed in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
(34 reference statements)
2
17
1
Order By: Relevance
“…In our study, the majority of strains were assigned to Enterovirus C (29/39), which is often described as the most common group circulating in sub-Saharan Africa [43,47]. Within this species, CVA20 and EV-C99 were the most common serotypes identified in our cohort.…”
Section: Discussionmentioning
confidence: 68%
“…In our study, the majority of strains were assigned to Enterovirus C (29/39), which is often described as the most common group circulating in sub-Saharan Africa [43,47]. Within this species, CVA20 and EV-C99 were the most common serotypes identified in our cohort.…”
Section: Discussionmentioning
confidence: 68%
“…While those where the same assay was used directly on fecal suspensions that did not show CPE in RD cell line, showed an abundance of EV-Cs [12]. Hence, the predominance of EV-Bs as documented by the PE-VP1-PCR assay, in this study, might be due to the fact that only samples that had yielded isolate in RD cell lines were selected and analyzed in this study.…”
Section: The Impact Of Mixture Resolving Assaysmentioning
confidence: 82%
“…RNA extraction, cDNA synthesis and snPCR were done as recently described (Faleye et al, 2016;Adeniji et al, 2017). Briefly, RNA extraction and cDNA synthesis were done using Jena Bioscience kits for RNA extraction and cDNA synthesis kits (Jena Bioscience, Jena, Germany), respectively, according to manufacturer's recommendations.…”
Section: Rna Extraction Cdna Synthesis and Seminested Polymerase Chamentioning
confidence: 99%
“…This role of NPEV-Cs in VDPV emergence exemplifies their importance, and the need to carefully catalogue their diversity and geographical distribution. It has however been shown (Sadeuh-Mba 2013, Adeniji and Faleye, 2014b, Faleye and Adeniji, 2015b, Adeniji et al, 2017) that the RD-L20B cell culture based algorithm (WHO, 2003;2004) recommended for and largely in use by the Global Polio Laboratory Network (GPLN) under-reports the preponderance of EV-Cs. This is because the L20B cell line component of the algorithm is largely specific for poliovirus detection due to its expression of the human poliovirus receptor (Pipkin et al 1993),while the RD cell line component that is supposed to be more promiscuous for EV detection is EV-B bias (Sadeuh-Mba 2013, Adeniji and Faleye, 2014a, Faleye and Adeniji, 2015a & b, Adeniji et al, 2017) We recently showed that EVs were present in about 46.7% of faecal samples from children <15 years old diagnosed with AFP but declared to be EV free by the RD-L20B cell culture based algorithm (WHO, 2003(WHO, , 2004.…”
Section: Introductionmentioning
confidence: 99%